Exploring Achievement Motivation on Employee Competency: Study at Health Service Institutions in Bandung, Indonesia. - Djadjat Suswanto (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This study investigates the impact of achievement motivation on competence, specifically examining the dimensions of knowledge, skill, and ability among employees in a healthcare setting. The primary objective is to understand how achievement motivation influences these critical areas of competence. Utilizing a quantitative research method, the study surveyed 66 employees at a healthcare institution in Bandung to gather relevant data. The results reveal that achievement motivation significantly affects achievement behaviors, leading to substantial improvements in employees' knowledge, skills, and abilities. This connection demonstrates the vital role that motivational factors play in enhancing professional competencies within a workplace environment. The novelty of this research lies in its focus on the interplay between achievement motivation and competence in a healthcare context, an area where such relationships have been less explored. The implications of these findings are noteworthy; organizations should prioritize initiatives that foster achievement motivation among employees. By doing so, they can enhance overall professional competence, which not only benefits individual employees but also contributes to higher standards of service delivery in the healthcare sector. Ultimately, this research underscores the importance of motivation in driving workforce development and improving public service outcomes.